Stoichiometric reductive C-N bond formation of arylgold(III) complexes with N-nucleophiles - Lavy, Séverine; Miller, Jeremie J.; Pažický, Marek; Rodrigues, Anne-Sophie; Rominger, Frank; Jäkel, Christoph; Serra, Daniel; Vinokurov, Nikolai; Limbach, Michael (Advanced synthesis & catalysis, 2010)
The reductive formation of substituted anilines from amines and three well-defined aryl- gold(III) complexes, i.e., dichloro(2,6-lutidine)phen- ylgold(III) (2), dichloro(2,6-lutidine)-p-tolylgold(III) (3), and chlorobis(triphenylphosphine)phenylgold(III) chloride (4) was studied. The reaction is stoichiometric in gold and represents a key step of a potential gold-catalyzed intermolecular amination reaction of arenes. It proceeds smoothly with a broad range of N-nucleophiles in the presence of sodium acetate (NaOAc) and enables the selective formation of N-substituted anilines in good yields. A mechanistic pathway is proposed and discussed as well.
Gesehen am 10.03.2023